TNF-α and TNFR1 responses to recovery therapies following acute resistance exercise - Townsend, Jeremy R.; Hoffman, Jay R.; Fragala, Maren S.; Jajtner, Adam R.; Gonzalez, Adam M.; Wells, Adam J.; Mangine, Gerald T.; Fukuda, David H.; Stout, Jeffrey R. (Frontiers in Physiology, 2015)
The purpose of this investigation was to compare the effect of two commonly used therapeutic modalities a.) neuromuscular electrical stimulation (NMES) and b.) cold water immersion (CWI) on circulating tumor necrosis factor alpha (TNF-α) and monocyte TNF-α receptor (TNFR1) expression following intense acute resistance exercise and subsequent recovery. Thirty (n=30) resistance trained men (22.5 ± 2.7 y) performed an acute heavy resistance exercise protocol on three consecutive days followed by one of three recovery methods (CON, NMES, and CWI). Circulating TNF-α levels were assayed and TNFR1 expression on CD14+ monocytes was measured by flow cytometry measured PRE, immediately post (IP), 30-minutes post (30M), 24 hours post (24H), and 48 hours post (48H) exercise. Circulating TNF-α was elevated at IP (p = 0.001) and 30M (p = 0.005) and decreased at 24H and 48H recovery from IP in CON (p = 0.015) and CWI (p = 0.011). TNF-α did not significantly decrease from IP during recovery in NMES. TNFR1 expression was elevated (p < 0.001) at 30M compared to PRE and all other time points. No significant differences between groups were observed in TNFR1 expression. During recovery (24H, 48H) from muscle damaging exercise, NMES treatment appears to prevent the decline in circulating TNF-α observed during recovery in those receiving no treatment or CWI.